Pengaruh Pencampuran Minyak Plastik (Low Density Polyetylene) dengan Pertamax Terhadap Profil Nyala Api Premixed - Dlofir, Aan Taufik; Hermawan, Dadang; Suwandono, Purbo (PROTON, 2023)
Plastic oil has great potential in the utilization of renewable energy both in Indonesia and in the world. Plastic oil (Low Density Polyethylene) is a fuel produced from the pyrolysis process of plastic waste and has an octane value of 81.6, so the quality of the fire is low. This study aims to improve the quality of plastic oil fire, namely by mixing plastic oil with Pertamax fuel. Plastic oil as the main material while Pertamax as an additional material, with variations in the composition of the Pertamax mixture ranging from 20% to 80%. Fire characteristics seen during the research process are flame height, flame temperature and flame color with premixed combustion using a burner. From the results of fire color research, there is an increase in blue color with each addition of Pertamax fuel to plastic oil. The blue color itself means that the fuel has a high calorific value. The increase also occurred in the height of the fire where the height of the fire increased with each addition of Pertamax fuel to plastic oil. Likewise, the fuel temperature increased when Pertamax was added, because Pertamax has a better heating value than plastic oil. From these three things it can be concluded that by providing the addition of Pertamax fuel, it is able to improve the quality of the flame from the processing of plastic waste, namely in the form of plastic oil.